2021
DOI: 10.3390/ijms222212388
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Lactobacillus plantarum Lac16 on Clostridium perfringens Infection-Associated Injury in IPEC-J2 Cells

Abstract: Clostridium perfringens (C. perfringens) causes intestinal injury through overgrowth and the secretion of multiple toxins, leading to diarrhea and necrotic enteritis in animals, including pigs, chickens, and sheep. This study aimed to investigate the protective effects of Lactobacillus plantarum (L. plantarum) Lac16 on C. perfringens infection-associated injury in intestinal porcine epithelial cell line (IPEC-J2). The results showed that L. plantarum Lac16 significantly inhibited the growth of C. perfringens, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 103 publications
(133 reference statements)
0
5
0
Order By: Relevance
“…In general, antimicrobial activity is the main mode of action of probiotics to prevent bacterial diseases ( Compaore et al., 2013 ; Nami et al., 2015 ; Du et al., 2019 ; Algburi et al., 2021 ; Zhou et al., 2021 ). Because no inhibitory activity on the growth of the S. braenderup H9812 was detected in vitro , prevention of B. subtilis LF11 from S. braenderup H9812 infection might be caused by other possible mechanisms including intestinal barrier ( Rao and Samak, 2013 ), coaggregation ( Collado et al., 2007 ), and signal interference ( Piewngam et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…In general, antimicrobial activity is the main mode of action of probiotics to prevent bacterial diseases ( Compaore et al., 2013 ; Nami et al., 2015 ; Du et al., 2019 ; Algburi et al., 2021 ; Zhou et al., 2021 ). Because no inhibitory activity on the growth of the S. braenderup H9812 was detected in vitro , prevention of B. subtilis LF11 from S. braenderup H9812 infection might be caused by other possible mechanisms including intestinal barrier ( Rao and Samak, 2013 ), coaggregation ( Collado et al., 2007 ), and signal interference ( Piewngam et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…This effect has been described as one of the mechanisms involved in the augmented growth performance in post-weaning piglets upon the treatment with the ZLP001 strain (Wang et al, 2012). Similar studies have demonstrated the ability of lactobacilli to modulate host defence peptides in porcine intestinal epithelial cells including L. reuteri I5007 (Liu et al, 2017), L. salivarius B1 (Zhang et al, 2011), and L. plantarum Lac16 (Zhou et al, 2021).…”
Section: Immunoregulatory Properties Of L Plantarum Isolatesmentioning
confidence: 64%
“…Huang et al demonstrated that Pediococcus can improve gastrointestinal motility and promote the production of beneficial bacteria that generate short-chain fatty acids [78]. Zhou et al also reported that Lactobacillus can attenuate cytotoxicity and intestinal barrier damage induced by Clostridium perfringens [79]. Furthermore, the abundance of Clostrid-ium_sensu_stricto was higher in fermentations treated with TCM-3 or TDM-2 than in the control group, which has also been reported to enhance short-chain fatty acid production [80].…”
Section: Discussionmentioning
confidence: 97%